Results in the Latin America and Caribbean Region 2018, Volume 11 - World Bank (World Bank, Washington, DC, 2022)
The Latin America and the Caribbean region has turned the corner, growing again after six years of economic slowdown. Economic growth is key to continue making progress on the social front and return to the poverty reduction gains that the region achieved over the first one and a half decades of the new century, when poverty was nearly halved. Moreover, now that growth is picking up it will be possible to focus even more on other areas that are also critical for the development of the region over the long-run, such as human capital, disaster risk management, good governance, and ensuring that the most vulnerable groups in society also benefit from growth.